A kind of flexural and tensile reinforced coarse aggregate ultra-high performance concrete and preparation method thereof

By combining carbon fiber with Mxene and mixing it with steel fiber, a coarse aggregate ultra-high performance concrete with enhanced bending and tensile resistance is prepared, which solves the shortcomings of existing concrete in terms of bending and tensile resistance, bending resistance, corrosion resistance and intelligent detection. Higher mechanical properties and structural safety are achieved.

CN118908664BActive Publication Date: 2025-01-21THE FIRST ENGINEERING COMPANY OF CCCC FOURTH HARBOUR ENGINEERING CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411138709.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-01-21
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

Existing steel fiber reinforced concrete has shortcomings in bending resistance, flexural resistance, corrosion resistance and intelligent inspection. Especially in large infrastructures that have been in service for a long time, materials are prone to fatigue, aging and corrosion, resulting in structural safety and reliability. Affected.

Method used

Carbon fiber is combined with the two-dimensional nanomaterial Mxene to prepare a carbon fiber composite material, which is mixed with steel fiber to form a coarse aggregate ultra-high performance concrete with enhanced flexural and tensile strength. This method not only improves the bending and tensile resistance, bending resistance and corrosion resistance of concrete, but also gives it good electrical conductivity and supports intelligent monitoring.

Benefits of technology

The composite material of carbon fiber and Mxene significantly improves the bending, tensile, bending and corrosion resistance of concrete, enhances its conductivity, supports intelligent detection, extends the service life of the structure, and improves safety and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention provides a flexural and tensile reinforced coarse aggregate ultra-high performance concrete and a preparation method thereof, comprising the following components: 300-800 parts of cement, 100-300 parts of fly ash, 100-300 parts of ceramic powder, 200-300 parts of silica ash, 500-800 parts of sand, 300-600 parts of crushed stone, 10-25 parts of polycarboxylic acid water reducer, and 150-200 parts of water; and also comprising MXene-carbon fiber composite material and steel fiber. The MXene-carbon fiber composite material is 0.2% to 2.0% of the total volume of concrete; and the steel fiber accounts for 0.5% to 2.0% of the total volume of concrete. The loading of MXene makes the carbon fiber more hydrophilic and rough, reduces the attachment of bubbles on the fiber surface and the generation of voids, and improves the compactness of the concrete; at the same time, MXene increases the bonding force, toughness and impact resistance of the carbon fiber / epoxy resin composite material; in addition, the conductive material MXene and the carbon fiber both increase the conductivity of the concrete. The present invention utilizes the mixed doping of carbon fiber composite materials and steel fibers to reduce the overall density of the fiber part and the dead weight of concrete, thereby obtaining a concrete product with enhanced toughening and chemical corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to flexural and tensile-reinforced coarse aggregate ultra-high performance concrete and a preparation method thereof. Background Art

[0002] Ordinary concrete is a brittle material with low tensile strength, low ultimate elongation, and a large number of micro cracks inside. External loads cause micro cracks to gradually expand and eventually form macro cracks, leading to material damage. At present, there are many studies on adding fibers as supporting materials to cement matrices to prepare fiber-reinforced concrete. Although steel fiber materials are widely used and have high mechanical strength, they have certain limitations in properties, such as easy corrosion, high brittleness, and easy bending and breaking. Moreover, for concrete that participates in the load-bearing of ultra-large span space structures such as large-span bridges, its service life is usually as long as a hundred years. It has been subjected to various environmental loads and rain and snow for many years. The material itself is constantly fatigued and aged, which eventually causes corrosion and fracture of concrete and cracking and even collapse of building materials. Therefore, higher requirements are put forward for concrete in terms of mechanical properties such as strengthening and toughening, damping resistance, fatigue resistance, and corrosion resistance.

[0003] At the same time, for large-scale infrastructure construction facilities, especially components with a long service life, it is necessary to monitor and diagnose stress, strain, cracks and damage from time to time. However, the resistivity of steel fiber reinforced concrete is too high and its pressure sensitivity is poor, which is not conducive to intelligent detection of concrete. It is urgent to conduct research on new fiber composite materials and reinforced concrete to meet higher standards of infrastructure needs. Summary of the invention

[0004] In order to solve the above problems, the purpose of the present invention is to provide a flexural and tensile reinforced coarse aggregate ultra-high performance concrete and its preparation technology. Carbon fiber is loaded with two-dimensional nanomaterial Mxene and combined with epoxy resin to prepare a carbon fiber composite material, which is then mixed with steel fiber. The ultra-high performance concrete prepared can not only improve its flexural, tensile, folding and corrosion resistance on the basis of the high compressive performance of the original steel fiber reinforced concrete, but also give the concrete good electrical conductivity, which can provide a basis for embedding sensors in key parts of infrastructure and realizing intelligent monitoring.

[0005] The technical solution for achieving the purpose of the present invention is as follows:

[0006] On one hand, the present invention provides a flexural and tensile reinforced coarse aggregate ultra-high performance concrete, which comprises the following components by weight: 300-800 parts of cement, 100-300 parts of fly ash, 100-300 parts of ceramic powder, 200-300 parts of silica fume, 500-800 parts of sand, 300-600 parts of crushed stone, 10-25 parts of polycarboxylate water reducer, and 150-200 parts of water; the concrete also comprises MXene-carbon fiber composite material and steel fiber material; the MXene-carbon fiber composite material accounts for 0.2% to 2% of the total volume of the concrete; the steel fiber material accounts for 1% to 2% of the total volume of the concrete, and the MXene-carbon fiber composite material is prepared by the following steps:

[0007] (1) Oxidative modification of carbon fiber: The carbon fiber tow is cut by an oxidant method, and then immersed in a strong acid solution for oxidation. After the immersion, the carbon fiber is repeatedly rinsed with water until the cleaning solution is neutral; after drying, the oxidized carbon fiber is obtained.

[0008] Preferably, the carbon fiber is recycled carbon fiber, and the size of the cut carbon fiber tow is length×width×height=(3-8) mm×1 mm×1 mm.

[0009] Preferably, the strong acid used is nitric acid with a concentration of 60-80wt%; the oxidation time is 3-6h, and the soaking temperature is 50-90°C; the oxidation and rinsing operations are both shaken on a shaking table with a shaking frequency of 30-50rpm; and the drying temperature is 60-100°C.

[0010] The amphiphobic nature and chemical inertness of recycled carbon fiber result in weak interfacial bonding forces (van der Waals forces and uncertain covalent bonds) between it and the matrix, which can easily cause interlaminar fractures in the composite material and affect the overall mechanical properties of the composite material; the surface of the oxidized recycled carbon fiber is rich in oxygen groups, hydroxyl groups and carboxyl functional groups, which are beneficial to electrostatic attraction with polyethyleneimine, formation of hydrogen bonds and combination with strong polar groups of MXene.

[0011] (2) Loading of Mxene: Disperse Mxene in an ethanol solution and perform ultrasonic dispersion; immerse the oxidized recovered carbon fiber in a polyethyleneimine solution, a Mxene solution, and a glutaraldehyde solution in turn, and take it out after each immersion and wash it thoroughly; finally, dry it to obtain the Mxene-loaded carbon fiber.

[0012] Preferably, Mxene is Ti3C2T x 、Ti2CT x 、V2CT x 、Nb2CT x One of the following, where T x is -OH functional group or / and -F functional group; more preferably Ti3C2T x .

[0013] MXene is a two-dimensional transition metal carbide or carbonitride with the chemical formula M n+1 X n T x (Where M is an early transition metal, X represents carbon / nitride, T x The terminal active groups include -O, -OH and / or -F functional groups), which can be prepared by selectively removing the A atomic layer in the MAX phase by HF and / or HCl etching, alkaline etching, electrochemical etching and molten salt etching (M is an early transition metal, A is a main group element, and X is C or N). The MXene material used in the present invention is Ti3C2Tx obtained by etching Ti3AlC2 by alkaline hydrothermal method, and its terminal T x It is composed entirely of -O, -OH groups and does not contain toxic -F groups.

[0014] Preferably, the ultrasonic dispersion power of Mxene is 80-100 W, the ultrasonic time is 1-3 h, and the ultrasonic temperature is maintained at no more than 25° C. using an ice water bath.

[0015] Preferably, the concentration of the Mxene solution is 0.2wt%-2.0wt%, and the loading time is 1-2h; further preferably, the concentration of the Mxene is 0.5wt%-1.0wt%.

[0016] Preferably, the polyethyleneimine used is linear, with a molecular weight between 1000-70000Da; more preferably, the molecular weight is between 10000 and 70000Da.

[0017] Preferably, the concentration of the polyethyleneimine solution is 0.5-2 g / L, and the immersion time is 0.5-1 h; the concentration of the glutaraldehyde solution is 0.2-1.2 wt %, and the cross-linking time is 8-30 min.

[0018] Preferably, the Mxene-carbon fiber composite material accounts for 0.5% to 1.2% of the total volume of the concrete, and more preferably, the Mxene-carbon fiber composite material accounts for 0.8% to 1% of the total volume of the concrete.

[0019] Unless otherwise specified in the present invention, the immersion temperature is preferably room temperature.

[0020] Mxene material has the advantages of high mechanical strength, thermal conductivity, electrical conductivity, corrosion resistance and large specific surface area, and the active groups on the surface make its combination with carbon fiber have high plasticity; the impregnation of polyethyleneimine increases the surface energy, and the free protonated amino groups make the carbon fiber surface positively charged, providing more anchor points and stronger electrostatic attraction for the full embedding of Mxene; the strategy of introducing the fiber structure by using the mechanical interlocking structure of polyethyleneimine and glutaraldehyde further strengthens the load stability and adaptability of Mxene.

[0021] (3) Preparation of MXene-carbon fiber composite material: The carbon fiber mixed solution obtained in step (2) is immersed in an epoxy resin solution to obtain a prepreg; a compression molding process is adopted to place the prepreg between an upper and a lower mold, and the prepreg is cured under high temperature and high pressure for a certain period of time; after the curing is completed, washing, drying and post-processing operations are performed to obtain a MXene-carbon fiber composite material.

[0022] Preferably, the epoxy resin solution includes epoxy resin and amine curing agent in a mass mixing ratio of (10-20):1.

[0023] The curing agent includes any one of aliphatic polyamines such as ethylenediamine, hexamethylenediamine diethylaminopropylamine, etc. The models used in the present invention are TDE-85 epoxy resin and DDS amine curing agent.

[0024] Preferably, the compression molding pressure is 5-30 MPa, the curing time is 5-10 h, and the curing temperature is 120-150° C.;

[0025] The size of the final prepared carbon fiber composite material specimen is 10mm×2mm×2mm.

[0026] MXene improves the distribution of carbon fibers and elements, making them more hydrophilic and rough, allowing water to easily enter the internal space of concrete, reducing the attachment of bubbles to the fiber surface and the generation of voids; MXene improves the surface energy of carbon fibers and greatly improves the interfacial adhesion; the residual hydroxyl, carbonyl, anhydride and other active groups on the surface of oxidized carbon fibers and the Tx groups on the surface of MXene can be intercalated and covalently bonded with epoxy monomers, effectively improving the covalent bond strength between interfaces and significantly improving the toughness, impact strength and crack deflection of the composite materials.

[0027] On the other hand, the present invention also provides a method for preparing flexural and tensile reinforced coarse aggregate ultra-high performance concrete, comprising the following steps: firstly adding the mixed aggregate and the MXene-carbon fiber composite material into a mixer according to the proportion, and adding 20% ​​of water for wet mixing for 2 minutes to obtain wet-mixed aggregate; at the same time, adding cement, fly ash, ceramic powder, silica fume, polycarboxylic acid water reducer and water in another mixer in sequence, stirring for 2 minutes, adding steel fibers multiple times while stirring, to obtain cement slurry containing steel fibers; finally, pouring the cement slurry containing steel fibers into the wet-mixed aggregate, stirring for 3 to 4 minutes, to obtain the ultra-high performance concrete.

[0028] Beneficial effects of the present invention:

[0029] The invention provides a flexural and tensile reinforced coarse aggregate ultra-high performance concrete. By selecting a low-density carbon fiber / resin composite material to replace part of the steel fibers, the overall density of the reinforced fiber part is reduced, the dead weight of the unit fiber concrete is reduced, and the sinking of the steel fibers during the vibration and curing process is alleviated, which is conducive to the uniform dispersion of the fibers in the concrete. The carbon fiber has the advantages of light weight, low cost, high modulus, good toughness, high temperature resistance and corrosion resistance. The carbon fiber composite material composed of the carbon fiber and the resin matrix improves the chemical corrosion resistance and yield toughness of the concrete, and overcomes the shortcomings of the steel fibers such as large brittleness and easy corrosion. In addition, the conductive carbon fiber and the Mxene material also improve the conductivity of the concrete, which is conducive to the realization of intelligent detection of the concrete.

[0030] The surface of carbon fiber is modified with the functional groups of polyethyleneimine, which can provide more active sites and improve the subsequent loading efficiency and stability of Mxene. At the same time, it also improves the interfacial adhesion and strengthens the cross-linking between the fiber and the resin matrix. The long chain structure and low elastic modulus of polyethyleneimine can also absorb impact energy and enhance the strength and toughness of carbon fiber.

[0031] On the one hand, the MXene loaded in the MXene-carbon fiber composite material fills the pores between the carbon fiber and the concrete, improving the density of the concrete; on the other hand, it changes the distribution of elements on the surface of the carbon fiber, improves the surface hydrophilicity and roughness, and makes it easier for the resin matrix to spread and infiltrate; and when the concrete is prepared, water is more likely to enter the internal space of the concrete, reducing the attachment of bubbles on the fiber surface and the generation of voids. Secondly, MXene forms an interface layer of a certain thickness between the carbon fiber surface and the resin matrix, which can disperse part of the impact destructive energy, limit the development of tiny cracks, and further improve the toughness and impact resistance of the reinforced carbon fiber composite material.

[0032] The present invention adopts waste carbon fiber for secondary recycling, which not only reduces production costs, but also effectively prevents environmental pollution caused by incineration / landfill and other disposal of waste carbon fiber, which is beneficial to reducing carbon emissions and implementing the "dual carbon" strategy. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] In the examples, the experimental methods used are all conventional methods unless otherwise specified; the materials, reagents, etc. used are all conventional products that can be obtained commercially unless otherwise specified.

[0035] The main raw materials involved in each embodiment and comparative example are as follows:

[0036] Filamentary waste carbon fiber, Shandong Carbon Sink Renewable Resources Co., Ltd.;

[0037] The cement was 52.5 grade P·Ⅱ cement, Yingde Conch Cement Co., Ltd.;

[0038] The fly ash is first-grade fly ash from power plant, Guangzhou Hengyun Thermal Power Co., Ltd.;

[0039] Ceramic powder, 1000 mesh, Tianjin Hongyan Tianshan Stone Nanotechnology Co., Ltd.;

[0040] Silica fume, Guangdong Jusan Industrial Co., Ltd.;

[0041] Steel fiber, end hook type, equivalent diameter 2mm, aspect ratio 60, tensile strength above 2000Mpa, Guangdong Jusan Industrial Co., Ltd.;

[0042] Polycarboxylate water reducer, water reduction rate 25-45%, Sika (China) Co., Ltd.;

[0043] Ethanol, 99% AR, Chengfeng Chemical;

[0044] Technical grade glutaraldehyde, 50%, MacLean Reagent Company;

[0045] Polyethylenimine, 99% AR, 1000, 10000, 70000Da, Sigma Reagent Company;

[0046] Epoxy resin, TDE-85, Mw600, 99% AR, Hubei Xingyinhe Chemical Co., Ltd.;

[0047] Amine curing agent, DDS amine curing agent, Shandong Mobai Chemical Co., Ltd.

[0048] Mxene, Ti3C2T X Powder, Xianfeng Nanomaterial Technology Co., Ltd.

[0049] Example 1

[0050] The invention discloses a flexural and tensile-reinforced coarse aggregate ultra-high performance concrete, which includes the preparation of Mxene-carbon fiber composite materials and the preparation of flexural and tensile-reinforced coarse aggregate ultra-high performance concrete doped with Mxene-carbon fiber composite materials.

[0051] The preparation steps of Mxene-carbon fiber composite material are:

[0052] (1) Oxidation modification of carbon fiber: The carbon fiber was cut into strips of 5 mm × 1 mm × 1 mm, and was immersed in a 65 wt% nitric acid solution at 70°C for oxidation treatment for 4 h. After the immersion, the carbon fiber was repeatedly rinsed until the cleaning solution was neutral; and then dried in an oven at 60°C to obtain oxidized carbon fiber;

[0053] Table 1 Performance parameters of recycled carbon fiber

[0054]

[0055] (2) Loading of Mxene: Mxene was dispersed in a 50 vol% ethanol solution, and the Mxene was ultrasonically dispersed for 1 h under 100 W ultrasonic crushing to obtain a 1.0 wt% Mxene solution; 100 parts of oxidized carbon fibers were sequentially immersed in a 2 g / L polyethyleneimine solution, an Mxene solution, and a 0.8 wt% glutaraldehyde solution for cross-linking; the immersion time was 45 min, 90 min, and 20 min, respectively. After each immersion, the carbon fibers were taken out and washed thoroughly with a 50 vol% ethanol solution; and dried in an oven at 60 ° C to obtain Mxene-loaded carbon fibers;

[0056] (3) Preparation of Mxene-carbon fiber composite materials: 70 parts of Mxene-loaded carbon fibers were immersed in 30 parts of a mixed solution of epoxy resin and DDS in a mass ratio of 10:1 to obtain a prepreg; a compression molding process was used to place the prepreg between an upper and lower mold and close the mold; the prepreg was cured at 120°C and 15 MPa for 6 hours; after the curing was completed, washing, drying and post-processing were performed to obtain a Mxene-carbon fiber composite material.

[0057] Post-processing operations mainly include grinding, cutting, painting, polishing, etc. of the cured carbon fiber composite material to reduce deformation and warping of the product and facilitate customized size. The final size of the prepared carbon fiber composite material sample is 10mm×2mm×2mm.

[0058] The preparation steps of the flexural and tensile reinforced coarse aggregate ultra-high performance concrete are as follows: first, 800 parts of sand, 500 parts of crushed stone and 1.0 vol% of MXene-carbon fiber composite material are added to a mixer, and 40 parts of water are added for wet mixing for 2 minutes; at the same time, 500 parts of cement, 100 parts of fly ash, 160 parts of ceramic powder, 200 parts of silica fume are added in sequence in another mixer, 10 parts of polycarboxylic acid water reducer and 152 parts of water are added and stirred for 2 minutes, and 1.0 vol% of steel fiber is added multiple times while stirring to obtain a cement slurry containing steel fiber; finally, the cement slurry containing steel fiber is poured into the wet mixed aggregate and stirred for 3 to 4 minutes to obtain the ultra-high performance concrete.

[0059] Example 2-Example 6

[0060] The operation is the same as in Example 1, except for the volumetric dosage of the Mxene-carbon fiber composite material. The specific addition amount is shown in Table 2.

[0061] Example 7-Example 10

[0062] The operation is the same as in Example 3, except for the Mxene concentration in step (2). The specific concentration parameters are shown in Table 2.

[0063] Example 11-Example 12

[0064] The operation is the same as that of Example 3, except that the molecular weight of polyethyleneimine in step (2) is replaced by 1000Da and 70000Da respectively.

[0065] Comparative Example 1

[0066] A concrete, the specific preparation steps are: firstly, 600 parts of sand and 800 parts of crushed stone are added into a mixer, and 40 parts of water are added and wet-mixed for 2 minutes to obtain wet-mixed aggregate; at the same time, 500 parts of cement, 100 parts of fly ash, 160 parts of ceramic powder, 200 parts of silica fume are added in sequence into another mixer, 10 parts of polycarboxylate water reducer and 152 parts of water are added and stirred for 2 minutes, and steel fiber with a volume fraction of 1.0% is added multiple times while stirring to obtain cement paste containing steel fiber; finally, the cement paste containing steel fiber is poured into the wet-mixed aggregate, stirred for 3-4 minutes to obtain concrete.

[0067] Comparative Example 2

[0068] Step (2) in Example 1 is omitted, that is, the carbon fiber is not loaded with Mxene; other operations and parameters are the same as in Example 1.

[0069] Comparative Example 3

[0070] The operation is the same as that of Example 3, except that step (2) is to omit the impregnation treatment of the oxidized carbon fibers with polyethyleneimine and glutaraldehyde, that is, 100 parts of the oxidized carbon fibers are directly immersed in the uniformly dispersed Mxene solution, and other conditions remain unchanged.

[0071] Table 2 Raw material parameters for preparing concrete in various embodiments and comparative examples

[0072]

[0073] In all embodiments and comparative examples, the raw materials were mixed according to the above requirements to obtain a fresh mixture, which was poured into a test mold and placed on a vibration table for 5 minutes to form. After demolding, the mixture was cured for 7 days and 28 days respectively using a standard curing method.

[0074] Compressive strength test: carried out in accordance with the national standard GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Ordinary Concrete", the concrete specimen size is 100mm×100mm×100mm.

[0075] Impact test: The drop hammer impact test was carried out in accordance with the standard GB / T 21120. The mass m of the hard steel ball was 3kg, and the free fall height h of the steel ball was 45cm. After each impact, the surface of the specimen was carefully checked for cracks or broken into pieces, and the number of impacts N1 and N2 of the initial crack and damage of the specimen were recorded respectively. The initial crack impact energy W1 and the damage impact energy W2 were calculated according to the formula W=Nmgh.

[0076] Flexural tensile strength test: According to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Ordinary Concrete", the flexural tensile strength is measured by three-point loading method, and the loading speed is 0.08MPa / s.

[0077] Sulfate erosion test: Referring to GB / T 749-2008 "Test Method for Sulfate Erosion Resistance of Cement", the cured concrete specimens were immersed in clean water and 10% sodium sulfate and 5% magnesium sulfate composite salt corrosion solution (the pH of the solution was maintained at 6-8). The sulfate resistance level of the test was KS90, so 90 dry-wet alternating tests of sulfate solution were conducted. The changes in weight and compressive strength before and after the erosion age were measured. Compressive strength corrosion resistance coefficient = compressive strength in salt solution / compressive strength in clean water.

[0078] Conductivity test: The concrete test block is dried in advance, and its resistance is tested using an AC impedance device at a frequency of 100 Hz. The conductivity ρ of the material is calculated according to the following formula:

[0079]

[0080] Where R is the material resistance, Ω; A is the cross-sectional area through which the current passes, m 2 ; L is the length of the test material, m. The electrical conductivity of the concrete test blocks of each embodiment and comparative example is shown in Table 3.

[0081] Table 3 Electrical conductivity test results of concrete of each embodiment and comparative example

[0082] sample Conductivity (7d) Conductivity (28d) Example 1 0.20 0.18 Example 2 0.45 0.41 Example 3 0.83 0.53 Example 4 1.02 0.56 Example 5 1.08 0.63 Example 6 1.12 0.71 Example 7 0.43 0.22 Example 8 0.83 0.56 Example 9 0.91 0.62 Example 10 1.05 0.65 Embodiment 11 0.56 0.29 Example 12 0.78 0.48 Comparative Example 1 0.02 0.03 Comparative Example 2 0.20 0.11 Comparative Example 3 0.60 0.48

[0083] The relevant mechanical test data of the embodiments and comparative examples are shown in Table 4.

[0084] Table 4 Mechanical test results of concrete of each embodiment and comparative example

[0085]

[0086] From Comparative Example 1, the single addition of steel fiber has improved the structural integrity of the reinforced concrete, but the electrical conductivity is weak, the corrosion resistance is poor, the brittleness is large, and the impact resistance is too poor.

[0087] When carbon fiber composite materials are mixed with steel fibers, not only the bridging effect of the fiber part is strengthened, but also the width of the aggregate-matrix interface is significantly reduced or even the interface is eliminated; as in Examples 1-6, at appropriate dosages, the tensile strength and impact toughness of concrete are improved, effectively resisting the formation and expansion of cracks, and its flexural tensile strength is ≥21MPa, preferably, its flexural tensile strength is ≥26MPa; carbon fiber composite materials also improve the corrosion resistance of concrete in sulfate environments and increase service life. After 90 hydrochloric acid corrosion tests, the corrosion resistance coefficient of the reinforced concrete is ≥90%, preferably, its corrosion resistance coefficient is ≥95%. However, the dosage of carbon fiber composite materials is not linearly related to the enhanced, toughened and corrosion-resistant properties of concrete. When carbon fiber is excessively doped, the compressive strength and yield toughness of concrete are reduced. This is because the fiber dispersion is difficult, agglomeration occurs, and the interaction and competition between the two fiber materials produce voids and defects, which also causes material waste.

[0088] With the increase of carbon fiber composite material content, the conductivity of reinforced concrete increases first and then tends to be flat; when the carbon fiber content is 0.6vol%, the increase shows an inflection point. The conductivity of specimens corresponding to different ages is significantly different, which is mainly related to the hydration process of cement. In the early stage of cement hydration, a large number of hydrated ions in the matrix play a conductive role; while the stage after cement solidification mainly relies on carbon fiber for conductivity.

[0089] Taking into account economic cost, agglomeration tendency, conductive effect and mechanical properties, the optimal dosage of carbon fiber composite materials is 0.5-1.2 vol%.

[0090] Compared with the comparative example 2 without Mxene loading, the Mxene nanostructure contained in the examples 3, 7-10 fills the voids inside the concrete, further improves the microstructure of the concrete, and increases the structural density of the fiber-reinforced concrete; and the MXene material is anchored in the carbon fiber with a pore structure, which effectively inhibits the accumulation of MXene sheets, increases the specific surface area of ​​the composite material, and also increases the flexibility of the concrete. With the increase of the Mxene loading concentration, the compressive strength and impact resistance show an overall trend of increasing first and then decreasing. This is because a higher concentration of Mxene will introduce more defects into the concrete, which will have an adverse effect on the performance of the concrete. It shows that there is also a critical value for the loading rate of Mxene, and the compressive strength and toughness are greatly improved when its dosage is in the range of 0.5% to 1.0%.

[0091] The conductivity of concrete gradually increases with the increase of Mxene concentration, and the increase shows an inflection point at a concentration of 0.5wt%. That is, when the Mxene concentration is below 0.5wt%, the conductivity increases sharply with the increase of Mxene concentration, indicating that the addition of Mxene has a significant effect on improving the conductivity of reinforced concrete; and when it continues to increase, the rising trend of conductivity gradually slows down, so the Mxene concentration range can be further optimized to 0.5% to 1.0%.

[0092] The Mxene impregnation concentrations of Example 3 and Comparative Example 3 are the same, but the mechanical properties of the concrete obtained in Comparative Example 3 are between those of Example 10 and Example 9, that is, the loading efficiency of Mxene is less than 75%, proving that the coating of carbon fiber with polyethyleneimine is beneficial to the loading of Mxene. Polyethyleneimine is positively charged and electrostatically attracts Mxene, and the cross-linking and interlocking of glutaraldehyde and polyethyleneimine further strengthen the loading stability.

[0093] The only difference between Example 3 and Example 11 and Example 12 is the different molecular weights of the polyethyleneimine used. The test results shown in Table 3 and Table 4 show that the chain length and structural characteristics of high molecular weight polyethyleneimine can improve the mechanical properties such as tensile strength and toughness of carbon fiber; enhance the overall strength of carbon fiber through hydrogen bonding force; and the long chain provides more active sites to improve the coating rate and polymerization strength; but when the molecular weight is too large, the polyethyleneimine with too long carbon chain wraps the Mxene into a group, causing the molecular chain to curl and shrink, which is not conducive to the overall strength of carbon fiber, and excessive cross-linking may occur, which leads to a decrease in the strength of the carbon fiber material.

[0094] The above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.

Claims

1. A flexural and tensile reinforced coarse aggregate ultra-high performance concrete, comprising the following components by weight: 300-800 parts of cement, 100-300 parts of fly ash, 100-300 parts of ceramic powder, 200-300 parts of silica fume, 500-800 parts of sand, 300-600 parts of crushed stone, 10-25 parts of polycarboxylic acid high-efficiency water reducing agent, and 150-200 parts of water; characterized in that: It also includes Mxene-carbon fiber composite material and steel fiber material, the volume of Mxene-carbon fiber composite material is 0.2% to 2% of the total volume of concrete, and the volume of steel fiber material is 1% to 2% of the total volume of concrete; the Mxene-carbon fiber composite material is prepared by the following steps: (1) Oxidation modification of carbon fiber: the carbon fiber tow is cut, immersed in a strong acid solution for oxidation, and then repeatedly rinsed with water until the cleaning solution is neutral; after drying, the oxidized carbon fiber is obtained; (2) Loading and curing of Mxene: Mxene was dispersed in ethanol solution and ultrasonically dispersed; The oxidized carbon fiber is sequentially immersed in a polyethyleneimine solution, a Mxene solution, and a glutaraldehyde solution, and after each immersion, it is taken out and fully washed, and then dried to obtain the Mxene-loaded carbon fiber; (3) Preparation of MXene-carbon fiber composite materials: immersing MXene-loaded carbon fiber materials in epoxy resin solution to obtain prepreg; using a compression molding process, placing the prepreg between upper and lower molds and closing the mold; curing under high temperature and high pressure for a certain period of time; After curing, washing, drying and post-treatment operations are performed to obtain the Mxene-carbon fiber composite material.

2. The concrete according to claim 1, characterized in that The carbon fiber described in step (1) is recycled carbon fiber; the size of the cut carbon fiber tow is length×width×height=(3-8) mm×1 mm×1 mm.

3. The concrete according to claim 1, characterized in that The strong acid in step (1) is nitric acid with a concentration of 60-80wt%, the oxidation time is 3-6h, and the soaking temperature is 50-90°C; the oxidation and rinsing are shaken on a shaking table with a shaking frequency of 30-50rpm; and the drying temperature is 60-100°C.

4. The concrete according to claim 1, characterized in that The Mxene in step (2) is Ti3C2T x 、Ti2CT x 、V2CT x 、Nb2CT x One of the following, where T x is an -OH functional group and / or a -F functional group.

5. The concrete according to claim 1, characterized in that The concentration of the Mxene solution in step (2) is 0.2wt%-2.0wt%; the power of ultrasonic dispersion is 80-100W, the ultrasonic time is 1-3h, and the ultrasonic temperature is maintained at no more than 25°C in an ice water bath; the loading time is 1-2h.

6. The concrete according to claim 1, characterized in that The polyethyleneimine in step (2) has a molecular weight between 1000-70000Da.

7. The concrete according to claim 1, characterized in that The concentration of the polyethyleneimine solution is 0.5-2 g / L, and the immersion time is 0.5-1 h; the concentration of the glutaraldehyde solution is 0.2-1.2 wt %, and the cross-linking time is 8-30 min.

8. The concrete according to claim 1, characterized in that The epoxy resin solution in step (3) comprises epoxy resin and amine curing agent in a mixing ratio of (10-20):1; the amine curing agent is an aliphatic polyamine, and the aliphatic polyamine is at least one of ethylenediamine and hexamethylenediamine diethylaminopropylamine; the weight of the epoxy resin accounts for 25%-35% of the weight of the carbon fiber composite material.

9. The concrete according to claim 1, characterized in that The curing time in step (3) is 2-6 hours, and the curing temperature is 120-150°C.

10. The method for preparing the flexural and tensile reinforced coarse aggregate ultra-high performance concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: According to the proportion, the mixed aggregate and the Mxene-carbon fiber composite material are first added to a mixer, and 20% of water is added and wet-mixed for 2 minutes to obtain wet-mixed aggregate; at the same time, cement, fly ash, ceramic powder, silica fume, polycarboxylic acid water reducer and water are added in another mixer in sequence, and stirred for 2 minutes, and steel fibers are added multiple times while stirring to obtain cement slurry containing steel fibers; finally, the cement slurry containing steel fibers is poured into the wet-mixed aggregate, and stirring is continued for 3 to 4 minutes to obtain the ultra-high performance concrete.

Citation Information

Patent Citations

  • Steel fiber concrete and preparation process thereof

    CN108264282A

  • Preparation method of carbon nanotube grafted carbon fiber

    CN116122040A